PROGNOSIS OF CARDIAC COMPLICATIONS IN ENDOCRINE SURGERY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Abstract:Thyroid disorders rank among the most prevalent conditions in endocrinology. Cardiovascular complications associated with these disorders not only impair patients' quality of life but also substantially elevate the risk of adverse surgical outcomes, with surgery being the primary definitive treatment. Consequently, many researchers in scientific literature regard both existing and emerging thyrotoxicosis as contraindications for elective thyroid surgery. Recent advancements have significantly broadened the scope of anesthesiological techniques employed during thyroid gland procedures. This article evaluates the preoperative preparation of patients with toxic and non-toxic goiter, as well as their management during the perioperative period.